Value homophily benefits cooperation but motivates employing incorrect social information. (21st February 2015) - Rauwolf, Paul; Mitchell, Dominic; Bryson, Joanna J.
Abstract: Individuals often judge others based on third-party gossip, rather than their own experience, despite the fact that gossip is error-prone. Rather than judging others on their merits, even when such knowledge is free, we judge based on the opinions of third parties. Here we seek to understand this observation in the context of the evolution of cooperation. If individuals are being judged on noisy social reputations rather than on merit, then agents might exploit this, eroding the sustainability of cooperation. We employ a version of the Prisoner׳s Dilemma, the Donation game, which has been used to simulate the evolution of cooperation through indirect reciprocity. First, we validate the proposition that adding homophily (the propensity to interact with others of similar beliefs) into a society increases the sustainability of cooperation. However, this creates an evolutionary conflict between the accurate signalling of ingroup status versus the veridical report of the behaviour of other agents. We find that conditions exist where signalling ingroup status outweighs honesty as the best method to ultimately spread cooperation. Abstract : Graphical abstract: Abstract : Highlights: We model the use of social norms and reputation to sustain cooperation. We examine the consequence of varying value-homophily in social interactions. Increasing value-homophily extends the potential for cooperation. It also creates selection pressure for ignoring accurate reputational information. Employing unjustified reputations is implicated in homophilous societies.